2021
DOI: 10.5114/hpr.2021.107336
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus anxiety, fear of COVID-19, hope and resilience in healthcare workers: a moderated mediation model study

Abstract: IntroductionIn the era of the global health crisis, mental health and well-being of people have been severely affected because of experiencing high levels of anxiety, stress, fear, and uncertainty related to COVID-19. This study investigated a moderated mediation model in which resilience mediated the link between coronavirus anxiety and fear of COVID-19, and this mediation effect was moderated by hope.Material and methodsA cross-sectional study was conducted on 168 healthcare workers (Mage = 29.19 ± 6.13 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 60 publications
2
27
2
Order By: Relevance
“…Other studies have also identified the protective role of resilience in disaster events (Labrague, 2018) and disease outbreaks (Duncan, 2020), as this quality could help nurses cope with and manage stressful situations. According to the study by Yıldırım and Güler (2021), resilience is an intermediary factor in the correlation between COVID-19 fear and anxiety (Yıldırım and Güler, 2021). In another research, Huffman et al (2021) reported that resilience is a protective factor against stress and other negative psychological factors resulting from the COVID-19 pandemic in healthcare workers (Huffman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also identified the protective role of resilience in disaster events (Labrague, 2018) and disease outbreaks (Duncan, 2020), as this quality could help nurses cope with and manage stressful situations. According to the study by Yıldırım and Güler (2021), resilience is an intermediary factor in the correlation between COVID-19 fear and anxiety (Yıldırım and Güler, 2021). In another research, Huffman et al (2021) reported that resilience is a protective factor against stress and other negative psychological factors resulting from the COVID-19 pandemic in healthcare workers (Huffman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that there is a statistically significant relationship between fear of COVID and mental health and hope. 41 Thus, the results from this study will help to understand the relationship between fear, hope, and mental health, and at the same time, these research results help teachers, health officials, and decision-makers on how to maintain good mental health during the COVID-19 pandemic.…”
Section: Rationale Of the Studymentioning
confidence: 86%
“…In sum, resilience acts as a psychological force to preserve mental health. 26 , 46 Therefore, there is a need to maximize support for nurses with high levels of stress and depression. 47 It is also suggested that, despite fear of infection, one of the reasons for staying and accepting risks in a resilient or altruistic manner is a sense of commitment and awareness as a nursing professional.…”
Section: Discussionmentioning
confidence: 99%